2019
DOI: 10.3389/fnana.2019.00005
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive 3D Microtomography of Cerebral Angioarchitecture Changes Following Ischemic Stroke in Rats Using Synchrotron Radiation

Abstract: A better understanding of functional changes in the cerebral microvasculature following ischemic injury is essential to elucidate the pathogenesis of stroke. Up to now, the simultaneous depiction and stereological analysis of 3D micro-architectural changes of brain vasculature with network disorders remains a technical challenge. We aimed to explore the three dimensional (3D) microstructural changes of microvasculature in the rat brain on 4, 6 hours, 3 and 18 days post-ischemia using synchrotron radiation micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Depending on the magnitude of X-ray absorption by the neurons and vasculature, differences in the gray values among tissues were determined, and microstructures of interest with a length of 1 cm for vascular analysis and a length of 0.5 mm for neuronal network analysis were extracted from the 3D models by segmentation. The 3D-rendered data were analyzed with the Image Pro Analyzer 3D (version 7.0, Media Cybernetics, Inc., Bethesda, MD, USA) to obtain quantitative data for the neuronal and vascular structures, as previously described [30,31], including the vascular volume fraction, vessel number, vessel thickness, vessel bifurcation density, vessel segment density, vessel segment length of the spinal cord, central sulcal artery (CSA) angle, soma volume fraction, soma density, and neurite length.…”
Section: D Image Reconstruction and Quantitative Analysismentioning
confidence: 99%
“…Depending on the magnitude of X-ray absorption by the neurons and vasculature, differences in the gray values among tissues were determined, and microstructures of interest with a length of 1 cm for vascular analysis and a length of 0.5 mm for neuronal network analysis were extracted from the 3D models by segmentation. The 3D-rendered data were analyzed with the Image Pro Analyzer 3D (version 7.0, Media Cybernetics, Inc., Bethesda, MD, USA) to obtain quantitative data for the neuronal and vascular structures, as previously described [30,31], including the vascular volume fraction, vessel number, vessel thickness, vessel bifurcation density, vessel segment density, vessel segment length of the spinal cord, central sulcal artery (CSA) angle, soma volume fraction, soma density, and neurite length.…”
Section: D Image Reconstruction and Quantitative Analysismentioning
confidence: 99%
“…The subsequent reconstruction of a 3D model for the vessels and vacuoles network found that the distribution of vacuoles is not uniform and the more severe the state of the disease, the greater the vasodilatation. Finally, a study by Luo et al (2019) analyzed brain samples from mice subjected to ischemia and described a new methodology that allowed the 3D analysis of the vascular repair in the ischemic lesion, both qualitatively and quantitatively, so that the morphology of the micro vessels could be visualized after the reconstruction of the vascular skeleton ( Luo et al, 2019 ).…”
Section: High-resolution Microtomography For the Study Of The Nervousmentioning
confidence: 99%
“…As a previous study [24] described, 10% chloral hydrate (0.4 ml/kg) was injected intraperitoneally to anesthetized those rats and x all the rats in the stereotaxic apparatus. The experimental SAH model consisted of a needle with a rounded tip and a side hole stereotaxic insertion into the prechiasmatic cistern.…”
Section: Rat Sah Modelmentioning
confidence: 99%